Public elementary schools' handling of student neglect and adjustment problems - Ikhrom Ikhrom; Dalmeri Dalmeri; Endang Wahyuni; Reza Kafipour (Frontiers in Education, 2023)
The challenge of being able to respond to student adjustment needs in elementary schools is a problem worldwide. In this manuscript, we offer one example from Indonesia. Using data from 15 public elementary schools from three small regions in Indonesia: Semarang, Surabaya, and Jakarta, we analyze conditions that result in neglect. Student neglect is any inappropriate action by an incompetent person that results in serious physical or emotional harm, or abuse, which presents a serious risk of harm to the student. The data were collected through documentation, interview, and observation. The study results showed no specific handling adjustment problems regulations and mechanisms, specialized professional staff handling adjustment, and specific room for handling adjustment problems within the public elementary school due to the unawareness, misunderstanding, ignorance, the less-caring educational system, and also the disconnection of the relationship between the educational institution and the community. The study suggests that student neglect on adjustment problems at public elementary schools should not be taken lightly because this can threaten the psychological condition of students in the future.